Evaluation of the optimal standardized ileal digestible tryptophan:lysine ratio in lactating sow diets - Greiner, L. (Transl Anim Sci, 2017)
Three hundred and fifteen primiparous and multiparous sows were evaluated in a study to determine the effect of standardized ileal digestible (SID) Trp:Lys ratio in lactating sow diets. Camborough sows (PIC USA, Hendersonville, TN) ranging from first parity to eighth parity were blocked by parity and randomly allotted to 1 of 4 experimental diets containing different levels of added L-Trp (0.006, 0.026, 0.045, and 0.064%, respectively) while soybean meal, 30% corn dried distiller's grain with solubles (DDGS), and L-Lys levels were held constant. The SID Lys level for the rations was 0.95% so that the SID Trp:Lys ratios were formulated to be 14, 16, 18, and 20%, respectively. All diets were formulated to have 3.2 Mcal ME/kg and to contain vitamins and minerals that exceeded NRC (1998) recommendations. Sows were fed twice a day with a Howema computerized feed system and were allowed a maximum intake (5.9 kg/d). Average daily feed intake had a tendency to be quadratically improved when the SID ratio was increased (5.11, 5.28, 5.24, 5.21 kg/d, P = 0.09). In addition, sow wean to estrus (6.71, 5.53, 5.58, 6.33, P < 0.02) was quadratically improved as SID Trp:Lys ratio increased. Percent of sows bred by 10 d (84.39, 90.82, 90.28, 90.61) was not linearly (P = 0.25) or quadratically (P = 0.40) improved. There was no difference in litter gain (2.44, 2.52, 2.60, 2.57 kg/d, P = 0.16). Based on a broken-line quadratic model, when sows are fed 30% DDGS, the SID Trp:Lys ratio of 17.6 is required for optimal sow average daily feed intake and 17.2 for wean to estrus interval.